Application of porous carbon modified catalytic adsorption integrated electrode and preparation method thereof
Patent Information
- Application Number
- CN202310921627.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-07-26
AI Technical Summary
为此,本发明的主要目的在于提供一种多孔炭修饰的催化吸附一体化电极的应用,旨在解决现有膜电极反应器电解碳酸氢钾原位还原CO2制备碳氢燃料过程中,存在阴极电极内部反应物质传输受限,CO2利用率低,目标产品法拉第效率(FE)低等问题
[0019]1)本发明所提供的多孔炭修饰的催化吸附一体化电极在电解碳酸氢盐中的应用,Ag纳米颗粒(Ag nanoparticles,Ag NPs)较为均匀的负载在多孔炭上,无团聚现象,使得AgNPs的活性位点充分暴露,有利于CO2还原反应的发生;且该催化吸附一体化电极为包括大孔结构、介孔结构和微孔结构,同时该催化吸附一体电极的比表面积大(120-1000m2/g),进而有效平衡了碳酸氢盐的传输过程与CO2的逃逸过程,进而提升了电解碳酸氢盐体系中产品FE、CO2利用率以及降低了槽电压电解等性能。
Smart Images

Figure CN116926599B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas diffusion electrode technology, specifically relating to the application and preparation method of a porous carbon-modified integrated catalytic adsorption electrode. Background Technology
[0002] With rapid societal development, the massive consumption of fossil fuels has significantly increased atmospheric CO2 concentrations, leading to environmental problems such as global warming. Therefore, there is an urgent need to develop an efficient strategy to reduce global CO2 concentrations. Electrochemical reduction of CO2 (ERC) is one of the most promising CO2 utilization strategies due to its mild reaction conditions, the ability to adjust reaction conditions to change the target product, and its potential for combination with renewable energy. This allows for the reduction of CO2 into renewable fuels while simultaneously utilizing unreliable renewable energy sources such as wind and electricity curtailment. However, ERC systems suffer from low CO2 utilization rates and high energy consumption in gaseous CO2 preparation, resulting in high energy consumption per unit of CO2 electrolysis and a complex carbon cycle, which hinders the industrial application of ERC technology.
[0003] Therefore, a pathway for in-situ CO2 reduction using electrolytic CO2 capture solution has been proposed. This pathway not only avoids energy-intensive steps such as desorption and compression in CO2 production but also simplifies the ERC (Extraction, Reduction, and Compression) technology for producing chemical products, making ERC technology more economical and technically feasible. However, current membrane electrode assembly (MEA) reactors for in-situ CO2 reduction using potassium bicarbonate to produce hydrocarbon fuels suffer from problems such as limited transport of reactants within the cathode electrode, low CO2 utilization, and low Faradaic efficiency (FE) of the target product. Therefore, optimizing the electrode structure, adsorbing CO2, and producing high-value-added products are crucial for the large-scale utilization of electrolytic bicarbonate.
[0004] In the bicarbonate electrolysis system, the bicarbonate solution is used as a carbon source and passed into the MEA electrolyzer. The H₂ generated by the bipolar membrane is utilized... + With HCO3 - The reaction occurs at the cathode / membrane interface, where a high local concentration of gaseous CO2 is formed, which then diffuses to the active sites to participate in the reaction and generate the target product. Since the cathode gas diffusion electrode is the site of the cathode reaction, mass transport within the electrode has a significant impact on the reaction. Currently used cathode gas diffusion electrodes still follow the electrode form of the gaseous CO2 electrolysis system (composed of a three-level structure of macroporous substrate, microporous layer, and catalyst layer). However, the mass transport processes involved in bicarbonate electrolysis differ from those in gaseous CO2 electrolysis. In the bicarbonate electrolysis system, CO2 is generated by H+... + With HCO3- The newly generated CO2 reactants are easily escaped through the electrolyte circulation and do not participate in the actual electrochemical reaction. Unlike the pure gaseous CO2 electrolysis system, which provides ample reactants, in the bicarbonate electrolysis system, adsorbing and capturing the generated CO2, increasing the local CO2 concentration, prolonging its contact time with the catalyst, and suppressing its escape are crucial for improving the electrochemical performance of this system. On the other hand, CO2 generation in the bicarbonate electrolysis system is limited by the bicarbonate transport rate; currently, research by Cuirtis et al. shows that gas diffusion electrodes without microporous layers enhance bicarbonate transport compared to electrodes with microporous layers, which is beneficial for H+ ion exchange. + With HCO3 - While CO2 is generated in situ, it still suffers from problems such as weak CO2 reduction, severe hydrogen evolution, and low single-pass CO2 conversion. For example, the CO2 utilization rate in the literature Haas T, Krause R, Weber R, et al. Technical photosynthesis involving CO2 electrolysis and fermentation[J]. 2018, 1(1): 32-9 is 12.5%; the CO2 utilization rate in the literature Salvatore DA, Weekes DM, He J, et al. Electrolysis of Gaseous CO2 to CO in a Flow Cell with a Bipolar Membrane[J]. 2017, 3(1): 149-54 is 3.0%; and the CO2 utilization rate in the literature Verma S, Hamasaki Y, Kim C, et al. Insights into the low overpotential electroreduction of CO2 to CO on a supported gold catalyst in an alkaline flow In electrolyzer[J].2017,3(1):193-8, the CO2 utilization rate is 4.1-8.2%; therefore, optimizing the structure of the gas diffusion electrode (GDE) to balance the transport process of bicarbonate and the escape process of CO2 is extremely important for improving the performance of the bicarbonate electrolysis system. Summary of the Invention
[0005] This invention aims to at least partially address one of the technical problems in related technologies. Therefore, the main objective of this invention is to provide an application of a porous carbon-modified integrated catalytic adsorption electrode, which addresses the problems of limited transport of reactants within the cathode electrode, low CO2 utilization, and low Faradaic efficiency (FE) of the target product in the existing membrane electrode reactor process for in-situ reduction of CO2 from potassium bicarbonate to produce hydrocarbon fuels. This invention also provides a method for preparing this porous carbon-modified integrated catalytic adsorption electrode.
[0006] The objective of this invention is achieved through the following technical solution:
[0007] In a first aspect, a porous carbon-modified integrated catalytic adsorption electrode is used in the electrolysis of bicarbonate, wherein the integrated catalytic adsorption electrode comprises silver nanoparticles and a porous material, and the silver nanoparticles are loaded on the surface of the porous material.
[0008] In some specific embodiments, the integrated catalytic adsorption electrode has a micron-scale porous structure, and the specific surface area of the integrated catalytic adsorption electrode is 120-1200 m². 2 / g.
[0009] In some specific embodiments, the average diameter of the pores in the micron-scale pore structure is 5-15 μm, and the micron-scale pore structure includes macroporous structures, mesoporous structures, and microporous structures.
[0010] In some specific embodiments, the mass fraction of the silver nanoparticles in the porous material is 65-85:1, and the loading is 1-5 mg / cm³. 2 .
[0011] Secondly, a method for preparing an integrated catalytic adsorption electrode modified with porous carbon according to the aforementioned applications includes the following steps:
[0012] Porous materials, silver nanoparticles, and binders are dispersed in an organic solvent and ultrasonically dispersed to form a uniform catalyst slurry. The catalyst slurry is then uniformly loaded onto a clean carbon paper surface using a spraying method.
[0013] In some specific embodiments, the mass ratio of the porous material to silver nanoparticles is (2-5):1.
[0014] In some specific embodiments, the loading of the silver nanoparticles is 1-5 mg / cm³. 2 .
[0015] In some specific embodiments, the ratio of the silver nanoparticles to the organic solvent and binder is 10 mg: (50-150) μl: (5-10) ml.
[0016] In some specific embodiments, the porous material is selected from activated carbon or carbon black; the binder is... Solution; the organic solvent is anhydrous ethanol.
[0017] In some specific embodiments, the specific surface area of the activated carbon is 800-1200 m². 2 / g, the specific surface area of the carbon black is 100-200m². 2 / g.
[0018] Compared with the prior art, the present invention has at least the following advantages:
[0019] 1) The application of the porous carbon-modified integrated catalytic adsorption electrode provided by this invention in the electrolysis of bicarbonate: Ag nanoparticles (Ag NPs) are uniformly loaded on the porous carbon without agglomeration, thus fully exposing the active sites of Ag NPs, which is beneficial to the occurrence of CO2 reduction reaction; moreover, the integrated catalytic adsorption electrode includes macroporous, mesoporous, and microporous structures, and has a large specific surface area (120-1000 m²). 2 / g), thereby effectively balancing the bicarbonate transport process and the CO2 escape process, thus improving the utilization rate of products FE and CO2 in the bicarbonate electrolysis system and reducing cell voltage electrolysis performance.
[0020] 2) The method for preparing the porous catalytic adsorption integrated electrode provided in this application utilizes porous carbon, a CO2 adsorption material, to modify an Ag-based gas diffusion electrode, thus constructing an integrated electrode with a CO2 adsorption layer and a catalytic layer. Simultaneously, the internal pore structure of the gas diffusion electrode (GDE) is controlled and optimized to enhance the CO2 adsorption performance within the electrode. This allows the catalytic adsorption integrated electrode to effectively adsorb H2 in the bicarbonate electrolysis system. + With HCO3 - The CO2 produced by the reaction reduces CO2 escape, improves the utilization rate of product FE and CO2, and lowers the cell voltage. It also has excellent CO2 utilization and operational stability, providing an effective approach for optimizing the cathode structure of electrolytic bicarbonate. Attached Figure Description
[0021] To more clearly illustrate the specific embodiments of the present invention, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.
[0022] Figure 1 This is a schematic diagram of the MEA-type flow reactor electrolysis bicarbonate testing system of the present invention;
[0023] Figure 2These are SEM images of the porous carbon-modified integrated catalytic adsorption electrode surfaces in Examples 2, 4, and the control group of the present invention.
[0024] Figure 3 The diagram shows the pore diameter distribution of the porous carbon-modified integrated catalytic adsorption electrode in Examples 2, 4 and the control group of the present invention.
[0025] Figure 4 These are permeability test graphs of the porous carbon-modified integrated catalytic adsorption electrode in Examples 2, 4 and the control group of the present invention;
[0026] Figure 5 The graphs show the CO2 adsorption characteristics of materials Ag, AC, and CB.
[0027] Figure 6 The elution test results for Ag, AC, and CB against N2 in this material are shown below.
[0028] Figure 7 The graph shows the changes in CO Faradaic efficiency, H2 Faradaic efficiency, and electrolyzer voltage during the constant current electrolysis of potassium bicarbonate using a porous carbon-modified integrated catalytic adsorption electrode in Examples 2, 4, and the control group of the present invention.
[0029] Figure 8 This is a graph showing the changes in CO2 electrolysis cell outlet concentration and CO2 utilization rate after the porous carbon-modified integrated catalytic adsorption electrode in Example 2 of the present invention has been running for 400 s at different current densities.
[0030] Figure 9 The graph shows the CO Faradaic efficiency and voltage variation of the porous carbon-modified integrated catalytic adsorption electrode in Example 2 of this invention during stability testing.
[0031] Figure 10 This is a graph showing the changes in CO2 utilization and electrolyte pH of the porous carbon-modified integrated catalytic adsorption electrode in Example 2 of the present invention during stability testing. Detailed Implementation
[0032] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The following embodiments are merely descriptive and not limiting, and should not be construed as limiting the scope of protection of the present invention.
[0033] When a quantity, concentration, or other value or parameter is described as a range, preferred range, or preferred upper and lower limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper or preferred values with any lower or preferred values, regardless of whether the range is specifically disclosed. Unless otherwise stated, the numerical range values listed herein include the endpoints of the range and all integers and fractions within that range.
[0034] Unless otherwise stated, all percentages, parts, ratios, etc. in this document are by weight.
[0035] The materials, methods, and embodiments described herein are exemplary and should not be construed as limiting unless otherwise stated.
[0036] In the following examples, the activated carbon, carbon black, and anhydrous ethanol used were all from Chengdu Kelong Chemical Co., Ltd., and the nano silver powder was from Shanghai Maclean Biochemical Technology Co., Ltd. The carbon paper (Avcarb MGL 190) is from DuPont, USA, and the carbon paper is from a fuel cell store.
[0037] In the following embodiments, the electrode morphology was characterized by field emission scanning electron microscopy (SEM, FEI Tecnai G2 F30); the CO2 adsorption characteristics of the carbon material were characterized by a physical adsorption analyzer (Micromeritics ASAP 2460); the electrode pore structure was characterized by mercury porosimetry (AutoPoreⅣ9510); and electrochemical tests were performed using the following methods:
[0038] Electrolysis of bicarbonate was performed using a MEA reactor on an electrochemical workstation (VMP3, Biologic, France) with a two-electrode system to evaluate the performance of electrolyzers under large-scale commercial current density conditions. The test system is as follows: Figure 1 As shown, 1M KOH electrolyte was introduced into the anode chamber at a flow rate of 20 ml / min, and 3M KHCO3 electrolyte was introduced into the cathode chamber at a flow rate of 20 ml / min. The carbon cathode electrode was 2×2 cm in size, and the nickel foam anode electrode was 3×3 cm in size. Before electrochemical testing, the electrolytes at both electrodes were continuously introduced into the electrolytic cell at a constant flow rate for 30 min to ensure that the electrolytes fully immersed the electrodes. During electrolytic cell operation, the headspace of the cathode electrolyte container was purged with N2 at a flow rate of 160 ml / min to purge and collect the reaction products. Before each collection of gaseous products, the electrolytic cell was kept running stably for 400 s. The gaseous products at the cathode were then sent to a gas chromatograph (GC-2030, Shimadzu Corporation, Japan) for analysis, and the Faraday efficiency and CO2 utilization rate of the target product were calculated. The Faraday efficiency was calculated using the following formula:
[0039]
[0040] Where m is the number of moles of the target product generated (mol), n is the number of electrons required to generate one mole of the target product, n = 2 for CO, F is the Faraday constant (96485 C / mol), and q is the total charge passing between the electrodes during the test (C).
[0041] The CO2 single-pass conversion rate is calculated using the following formula:
[0042]
[0043] Among them, [CO] and [CO2] outlet These represent the CO and CO2 outlet concentrations obtained from gas chromatography analysis and measurement, respectively.
[0044] Example 1
[0045] The method for preparing the porous carbon-modified catalytic adsorption integrated electrode in this application is as follows: 20 mg AC, 10 mg Ag NPs, and 55 μl... The catalyst was dispersed in 5 ml of anhydrous ethanol and ultrasonically dispersed for 60 min to form a uniform catalyst slurry. Then, the catalyst slurry was uniformly loaded onto a 4 cm thick substrate using a spraying method. 2 A clean carbon paper surface with a catalyst loading of 1 mg / cm³. 2 That is, to prepare a catalytic adsorption integrated electrode modified with porous carbon using porous materials (abbreviated as Ag+AC).
[0046] Example 2
[0047] 40 mg AC, 10 mg Ag NPs (Ag nanoparticles, Ag NPs) and 112 μl The catalyst was dispersed in 8 ml of anhydrous ethanol and ultrasonically dispersed for 60 min to form a uniform catalyst slurry. Then, the catalyst slurry was uniformly loaded onto a 4 cm thick substrate using a spraying method. 2 A clean carbon paper surface with a catalyst loading of 2 mg / cm³. 2 That is, to prepare a catalytic adsorption integrated electrode modified with porous carbon using porous materials (abbreviated as Ag+AC).
[0048] Example 3
[0049] 50 mg AC, 10 mg Ag NPs (Ag nanoparticles, Ag NPs) and 150 μl The catalyst was dispersed in 10 ml of anhydrous ethanol and ultrasonically dispersed for 60 min to form a uniform catalyst slurry. Then, the catalyst slurry was uniformly loaded onto a 4 cm thick substrate using a spraying method. 2 A clean carbon paper surface with a catalyst loading of 5 mg / cm³. 2 That is, to prepare a catalytic adsorption integrated electrode modified with porous carbon using porous materials (abbreviated as Ag+AC).
[0050] Example 4
[0051] The preparation method of the porous carbon-modified catalyst adsorption integrated electrode provided in Example 4 is basically the same as that in Example 2 in terms of composition and ratio, except that the activated carbon in the raw materials is replaced with carbon black; the preparation method is the same as that in Example 2; the porous carbon-modified catalyst adsorption integrated electrode (abbreviated as Ag+CB) prepared in this control group.
[0052] Control group:
[0053] 10 mg Ag NPs (Ag nanoparticles, Ag NPs) and 112 μl The catalyst was dispersed in 8 ml of anhydrous ethanol and ultrasonically dispersed for 60 min to form a uniform catalyst slurry. Then, the catalyst slurry was uniformly loaded onto a 4 cm thick substrate using a spraying method. 2 The clean carbon paper surface has a catalyst loading of 2 mg / cm³. 2 (Abbreviated as Ag).
[0054] Performance testing:
[0055] This application characterizes the performance of Ag+AC from Example 2 and Ag+CB from Example 4 (in the following performance tests, unless otherwise specified, Ag+AC refers to Ag+AC from Example 2 and Ag+CB refers to Ag+CB from Example 4), specifically:
[0056] 1. Morphological characteristics
[0057] The three integrated catalytic adsorption electrodes (Ag, Ag+CB, Ag+AC) prepared in the aforementioned examples (control group) were observed, and the results are as follows: Figure 2 As shown, the 300μm large-field SEM results qualitatively indicate that the Ag electrode has the richest micron-level pore content, the Ag+CB electrode has the least, and the Ag+AC electrode has a moderate level of micron-level pore content. Furthermore, the 2μm image reveals the dispersion of AgNPs in the catalyst layer. The figure shows that Ag NPs aggregation is extremely pronounced in the Ag electrode, covering most of the catalytic active sites and preventing them from participating in the CO2 reduction reaction. In the Ag+CB electrode, Ag NPs are uniformly dispersed with CB, and the aggregation of Ag NPs is significantly reduced. However, the alternating mixing of Ag NPs and CB still results in some Ag NPs being covered by CB and unable to participate in the reaction. Among the three types of electrodes, the Ag+AC electrode shows the most uniform loading of Ag NPs on the activated carbon surface, fully exposing the active sites of Ag NPs, which is beneficial for the CO2 reduction reaction.
[0058] 2. Mercury porosimetry test
[0059] Mercury porosimetry was performed on the three integrated catalytic adsorption electrodes (Ag, Ag+CB, Ag+AC) prepared in the aforementioned examples (control group) to obtain the pore structure distribution and permeability of the macropores inside the different electrodes. The results are as follows: Figure 3 As shown, most of the pores in all electrodes have a diameter of approximately 11 μm, and these pores primarily function as HCO3-. - The porosity of an electrode greatly influences its internal two-phase transport characteristics, as it serves as a transport channel for CO2 and products. The Ag electrode exhibits the richest pore structure, followed by the Ag+CB electrode with the least porosity, while the Ag+AC electrode falls in the middle, consistent with SEM characterization results. The permeability of the three electrodes is shown below. Figure 4 As shown, the Ag electrode exhibits the highest permeability at 2398.26 md, while the Ag+CB electrode has a permeability of only 1619.49 md. The Ag+AC electrode, however, has a significantly higher permeability than the Ag+CB electrode (2033.77 md). The test data all indicate that the Ag electrode has the richest pore structure and the highest permeability. While this structure enhances the transport rate of bicarbonate ions to the membrane surface, it also accelerates CO2 escape. The Ag+CB electrode has the least porosity and the lowest permeability. While this structure best inhibits CO2 escape and increases CO2 reaction time, it also reduces the transport rate of bicarbonate ions to the membrane surface, limiting the rate of in-situ CO2 generation at the membrane surface. Compared to the Ag and Ag+CB electrodes, the Ag+AC electrode ensures both the internal bicarbonate transport rate, guaranteeing sufficient CO2 production, and inhibits CO2 escape, thus increasing the CO2 reaction time.
[0060] 3. Adsorption characteristics
[0061] The CO2 adsorption characteristics of Ag, AC, and CB were characterized by CO2 adsorption-desorption tests, such as... Figure 5 As shown, Ag NPs exhibit almost no adsorption capacity for CO2; under standard conditions, the CO2 adsorption capacity is only 0.36 cm⁻¹. 3 / g, the CO2 adsorption capacity of CB reaches 18.1cm³. 3 / g, AC's CO2 adsorption capacity reached a maximum of 61.5cm³. 3 / g. Furthermore, the pore structure and specific surface area of Ag, AC, and CB were characterized by N2 adsorption-desorption tests, such as... Figure 6 As shown, Ag NPs do not have micro- or nano-pores inside, therefore their pore specific surface area is only 2.37 m². 2The internal pore structure of both CB and AC mainly consists of micropores (<2nm) and mesopores (2nm-50nm), with a small amount of macropores (>50nm). The presence of these hierarchical pore structures effectively promotes the adsorption of CO2 by carbon materials. AC exhibits a richer microporous and mesoporous pore structure than CB, with a BET specific surface area reaching 942.19 m². 2 / g, far higher than CB(163.50m 2 / g). Furthermore, due to the effective promotion of CO2 physical adsorption by micropores and mesopores, the abundant hierarchical pores give AC the strongest CO2 adsorption capacity. Uniformly mixing porous carbon with high specific surface area and strong CO2 adsorption capacity with Ag NPs can integrate the CO2 adsorption layer (AC / CB) with the catalyst layer (Ag NPs). The presence of the adsorption layer can inhibit CO2 escape, increase the CO2 concentration inside the electrode, and thus promote the electrochemical reduction of CO2.
[0062] 4. Effects of electrodes on the electrolysis of bicarbonate
[0063] like Figure 7 As shown, when Ag NPs are used as catalysts for the reduction of CO2 in the potassium bicarbonate electrolysis system, the output products consist of CO and H2, and the sum of the Faraday efficiencies for CO and H2 is approximately 100%. Figure 7 (a) It can be seen that the three electrode structures FE CO All of these decrease with increasing current density, with Ag, Ag+CB, and Ag+AC decreasing at a current density of 100 mA / cm². 2 The CO Faraday efficiencies were 40.91%, 49.62%, and 53.67%, respectively, while when the current density increased to 250 mA / cm², the efficiency decreased. 2 At these times, the CO Faraday efficiency decreased to 28.17%, 34.69%, and 39.65%, respectively. This phenomenon can be attributed to the fact that under high current density conditions, CO2RR requires the consumption of a large amount of reactants (including H2). + (and gaseous CO2), at this point, CO2 transport is mainly restricted, becoming the limiting step of CO2RR. Therefore, as the current density increases, the reactant supply becomes insufficient, but the H+ in the solution... + Abundant in content, the charge transferred to the cathode reacts with H under the action of Ag NPs. + The reaction produces H2, and the hydrogen evolution reaction intensifies with increasing current density. However, throughout the entire tested current density range, the CO Faradaic efficiency of the Ag electrode is lower than that of the carbon-modified electrode; Ag+AC exhibits a higher CO Faradaic efficiency compared to Ag+CB. At a current density of 150 mA / cm²... 2Under these conditions, the CO Faradaic efficiency of the Ag+AC electrode reaches 52.54%, which is higher than that of the Ag+CB electrode (43.47%), while the CO Faradaic efficiency of the Ag electrode is only 36.42%. Figure 7 (b) shows the hydrogen evolution faradaic efficiency of the three electrodes. It can be seen that the hydrogen evolution reaction is weakest at the Ag+AC electrode within the test current range, meaning that a larger proportion of the charge transferred to the cathode participates in CO2RR to generate CO. In summary, the Ag+AC electrode exhibits the highest CO faradaic efficiency and the lowest H2 faradaic efficiency. Under the condition that Ag NPs are used as catalysts, combined with morphological characterization data, the improvement in CO faradaic efficiency is mainly attributed to the use of porous carbon to modify the electrode, thereby controlling the electrode pore structure. This balances the bicarbonate and CO2 transport processes, allowing for rapid CO2 generation, increasing the internal CO2 concentration of the electrode, and maintaining a low escape velocity, ensuring sufficient CO2 participation in the reaction. Furthermore, the porous structure and high specific surface area of the porous carbon itself provide CO2 adsorption sites. Using it as an adsorption layer and uniformly mixing it with the Ag NPs catalyst layer can increase the internal CO2 concentration of the electrode. Numerous studies have shown that high CO2 concentrations are beneficial for promoting CO2RR and suppressing hydrogen evolution side reactions. Figure 7 (c) represents the cell voltage of the three electrodes. It can be seen that the cell voltage of the electrode modified with porous carbon material is lower than that of the Ag electrode in all test current density ranges. This is because the electrode modified with carbon material optimizes the material transport process inside the electrode and increases the CO2 concentration inside the electrode, which is beneficial to reducing the cell voltage.
[0064] 5. Electrode CO2 utilization rate
[0065] Using the Ag+AC electrode from Example 2, at current densities of 50, 100, and 200 mA / cm², respectively... 2 The test was conducted, and after 400 seconds of stable operation, gaseous products were collected. The outlet CO2 concentration was detected using a gas chromatograph, and the CO2 utilization rate was calculated. Figure 8 As shown in (a), at current densities of 50, 100, and 200 mA / cm² 2 At these times, the CO2 outlet concentrations were 6439.3, 10858.25, and 20343.95 ppm, respectively. It can be seen that the CO2 outlet concentration increases approximately proportionally with increasing current density, meaning that bicarbonate transport is unrestricted under high current density conditions and can react with H+ ions on the bipolar film surface. + Sufficient CO2 is generated to participate in the reaction. For example... Figure 8 As shown in (b), the CO2 utilization rate remained around 46% under different current density conditions, specifically at current densities of 50, 100, and 200 mA / cm². 2At that time, the CO2 utilization rates were 44.96%, 47.92%, and 47.23%, respectively, which means that the AC-modified Ag+AC electrode can effectively adsorb the generated CO2 and prevent it from escaping. Half of the CO2 generated on the surface of the bipolar film participates in the CO2RR reaction. Moreover, the CO2 utilization rate does not decrease with the increase of current density. The high CO2 utilization rate can greatly reduce the cost of subsequent product separation and improve the economic efficiency of the system.
[0066] 6. Electrode operational stability
[0067] To investigate the stability of the electrode operation, at 50 mA / cm 2 Under current density conditions, the performance of the device was tested to determine whether it would degrade during long-term electrolysis of potassium bicarbonate. The test results are as follows: Figure 9 and Figure 10 As shown, during the 12-hour stable operation, the voltage increased from 2.98V to 3.16V, a rise of only 0.18V. This slight increase occurred only in the first hour of operation, and the voltage remained stable for the subsequent 11 hours, demonstrating good voltage stability. Initially, the CO Faraday efficiency was only 33.54%. This was due to the incomplete equilibrium of mass transport processes within the electrode and the unstable local microenvironment. At this point, the hydrogen evolution reaction was severe. Since the equilibrium potential for the hydrogen evolution reaction is 0V vs RHE, which is higher than the equilibrium potential for CO2 reduction to CO (-0.1V vs RHE), the cell voltage was also low at this time. After the electrochemical reaction stabilized, the CO Faradaic efficiency reached 62.07% after 1 hour of operation. Due to CO2 consumption during prolonged operation, the CO Faradaic efficiency decreased with increasing time, dropping to 47.71% after 6 hours. At this point, the electrolyte was replaced, and the CO Faradaic efficiency recovered to 62.22% after 7 hours. It then slowly decreased again, and after a second electrolyte replacement at 11 hours, the CO Faradaic efficiency was 58.81%, indicating a slight decrease after 11 hours of operation. Simultaneously, during the reaction process, OH... - As CO2RR products accumulate, the pH of the electrolyte continuously increases. For example... Figure 10 As shown, with increasing running time, CO2 utilization rate first increases and then decreases. When running for 4 hours, CO2 utilization rate reaches its highest value of 68.61%, an increase of 23.19% compared to the CO2 utilization rate (45.42%) after 1 hour of operation. At this point, the CO Faradaic efficiency is 52.11%, only 9.96% lower than the 62.07% after 1 hour of operation. Therefore, by adjusting the electrolyte pH and potassium bicarbonate concentration, the concentration of CO or target product in the target product stream can be increased, thereby reducing product separation costs.
[0068] This invention uses carbon aluminate (AC) as an Ag NPs support. Ag NPs are uniformly loaded onto the AC surface through physical dispersion. Then, AC and Ag NPs are loaded onto carbon paper using a spraying method to construct a high-efficiency potassium bicarbonate electrolysis electrode. AC's high specific surface area and strong CO2 adsorption capacity make it more suitable for bicarbonate electrolysis systems. This invention, by using AC as an Ag NPs support to modify the electrode, successfully constructs an integrated CO2 adsorption and catalytic layer electrode, optimizes the internal pore structure of the electrode, and improves the mass transport process. Compared to using carbon aluminate (CB) as a support, it effectively prevents CO2 escape within the bicarbonate electrolysis system and increases the local CO2 concentration. Electrochemical tests show that this electrode can efficiently electrolyze potassium bicarbonate to produce CO at 100 mA / cm². 2 and 150mA / cm 2 The CO Faradaic efficiencies reached 53.67% and 52.54%, respectively; the electrolyzer voltages were 3.44V and 4.03V, respectively. Stability tests showed that the electrode could maintain high-efficiency operation for 11 hours, with the cell voltage increasing by only 0.18V (from 2.98V to 3.16V) and the CO Faradaic efficiency decreasing by only 3.26% (from 62.07% to 58.81%), while maintaining a CO2 utilization rate of 68.61%. In summary, this invention demonstrates that the porous carbon-modified catalytic adsorption integrated electrode can effectively adsorb CO2 in the bicarbonate electrolysis system, improving the product Faradaic efficiency and CO2 utilization rate, and providing an effective approach for optimizing the cathode structure of bicarbonate electrolysis.
[0069] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.
Claims
1. The application of a porous carbon-modified integrated catalytic adsorption electrode in the electrolysis of bicarbonate to produce CO, characterized in that, The porous carbon-modified catalytic adsorption integrated electrode comprises silver nanoparticles and a porous material, wherein the silver nanoparticles are loaded on the surface of the porous material. The porous carbon-modified catalytic adsorption integrated electrode is prepared by the following method: the porous material, silver nanoparticles, and a binder are dispersed in an organic solvent, ultrasonically dispersed to form a uniform catalyst slurry, and then the catalyst slurry is uniformly loaded onto a clean carbon paper surface using a spraying method. The porous material is selected from activated carbon or carbon black; the mass ratio of the porous material to the silver nanoparticles is (2-5):1; and the loading of the silver nanoparticles is 1-5 mg / cm³. 2 .
2. The application according to claim 1, characterized in that, The integrated catalytic adsorption electrode has a micron-scale porous structure and a specific surface area of 120-1200 m². 2 / g.
3. The application according to claim 2, characterized in that, The average diameter of the pores in the micron-scale pore structure is 5-15 μm, and the micron-scale pore structure includes macroporous structures, mesoporous structures and microporous structures.
4. The application according to claim 3, characterized in that, The ratio of the silver nanoparticles to the organic solvent and binder is 10 mg: (50-150) μl: (5-10) ml.
5. The application according to claim 4, characterized in that, A method for preparing a porous carbon-modified integrated catalytic adsorption electrode, characterized in that the binder is Nafion. ® Solution; the organic solvent is anhydrous ethanol.
6. The application according to claim 3, characterized in that, The specific surface area of the activated carbon is 800-1200 m². 2 / g, the specific surface area of the carbon black is 100-200 m² / g. 2 / g.
Citation Information
Patent Citations
Silver-based carbon dioxide reduction catalyst and preparation method thereof
CN111672505A
Bipolar membrane-based catalyst coated membrane electrode and application of bipolar membrane-based catalyst coated membrane electrode in electrocatalytic conversion of bicarbonate
CN116288465A
